Strategi Pelayanan Kartu Tanda Penduduk Elektronik Di Kabupaten Padang Lawas Utara - Harahap, Esmaitul Fitria; Gunawan, Syafri; Dalimunthe, Dermina (Jurnal El-Thawalib, 2023)
This study discusses the implementation of the electronic identity card service at the Department of Population and Civil Registration, North Padang Lawas Regency.  The method in this study uses a type of empirical normative research, namely an understanding of the law in terms of norms and the implementation of the rule of law in real behavior as a result of the application of legal norms, the approach taken by the researcher is the legal approach and the sociological legal approach, the data source used by the researcher is data  primary (obtained directly from the main source) secondary data (obtained from documents and books).  The data collection techniques carried out by researchers are observation (directly on the object of research), interviews (direct discussions with parties related to the research) and documentation (written or picture).  The data analysis technique used by the researcher is descriptive qualitative analysis, that is, efforts are made by working with data, organizing data, sorting it into manageable units, synthesizing it, looking for patterns, finding out what is important, what is learned, what is told to others.  The results showed that the implementation of the electronic identity card service for North Padang Lawas Regency was not in accordance with Law Number 25 of 2009 concerning Public Services.  And it should be carried out in accordance with a system where the public can obtain an e-KTP by inputting, processing and producing an e-KTP issuance output.  Supporting factors so that the implementation of the electronic identity card service runs well is the existence of an e-ID card, adequate budget and human resources so that the service can run smoothly.  And for the inhibiting factors, namely internet access that is less than optimal, the discipline of office employees who are still not punctual, inadequate facilities and infrastructure, completion times that are not as determined and also lack of public awareness.